Coated loom parts and manufacturing method
By forming a multi-layer coating structure on the knitting needles, combined with the composition and deposition technology of Cr, W, Si and N/C elements, the existing knitting needle coatings have been solved, and the service life and product quality of the knitting needles have been significantly improved.
Patent Information
- Application Number
- CN202411990403.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The existing knitting needles have high roughness and excessive hardness, resulting in short service life, not wear-resistant, wool and wire breakage, and cannot meet the same quality standards as imported knitting needles.
A multi-layer coating structure is adopted, including a base layer, a transition layer, a hardened wear-resistant layer and a surface layer, with specific components such as Cr, W, Si and N/C. The CrWSiN and CrWSiC layers are alternately deposited through vacuum furnace deposition technology to form a hardened wear-resistant layer of 6-12 layers.
It improves the service life of knitting needles, reduces production costs, ensures the continuity and quality of the yarn during the testing process, and exceeds the wear and bleaching of imported knitting needles.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to a loom component with a coating and a manufacturing method thereof, belonging to the field of surface treatment of loom components. The specific loom components include (groove needles, latch needles, yarn guide needles, sinkers and other winding parts). Background Art
[0002] The winding parts on the loom will wear out when in contact with the yarn for a long time during the weaving process. For example, worn knitting needles will cause yarn fuzzing and breakage, which will affect the quality of the cloth and need to be replaced regularly. The quality and service life of knitting needles determine the production cost and product quality of the enterprise. The industry has a strong demand for high-quality knitting needles, which are currently mainly imported.
[0003] In order to improve the quality of knitting needles, a layer of high-hardness wear-resistant metal coating is currently electroplated, sprayed, or PVD on the surface of the knitting needles. For example, in patent document CN 101787628 A, an oxide ceramic coating or a metal coating is plasma sprayed on the surface of the knitting needle. In patent document CN 217973595, arc discharge technology is used to evaporate the metal target material under vacuum conditions to form a 2300HV superhard layer on the surface of the knitting needle. In patent document CN 217251768 U, a layer of Ti or Cr alloy coating is PVD on the surface of the knitting needle, with a thickness greater than 6 microns, a hardness of 2800HV, and a surface roughness of less than Ra4.5 after eddy current polishing.
[0004] The existing technical methods have improved the quality of knitting needles to a certain extent, but there is still a certain gap compared with imported knitting needles. The main reason is that the coating roughness formed on the knitting needles by the existing technology is generally above Ra0.3, and the hardness is high and the film layer is thick. During use, there are problems such as short service life, poor wear resistance, fuzzing, and broken wires. Summary of the invention
[0005] The present invention aims at solving the deficiencies of the prior art and provides a loom component with a coating and a manufacturing method thereof.
[0006] To achieve the above-mentioned purpose, the present invention is implemented through the following technical scheme: a loom component with a coating, comprising a basic component body, on which a base layer, a transition layer, a hardened wear-resistant layer and a surface layer are sequentially arranged; wherein the base layer is a Cr layer, the transition layer is a CrN transition layer, the hardened wear-resistant layer is a CrWSiN and CrWSiC layer, the surface layer is CrWSiNC, and the components of Cr, W and Si in the coating account for 30-50%, 23-33% and 27-37% respectively.
[0007] The specific features of this solution are that the proportions of Cr, W and Si in the coating are 35-45%, 25-30% and 30-35% respectively. The hardened wear-resistant layer is formed by alternating deposition of CrWSiN or CrWSiC, with a total of 6-12 layers. The thickness of the hardened wear-resistant layer is 1.85-3.8μm.
[0008] The preparation steps of the hardened wear-resistant layer are as follows: c1. Introduce 130-220 SCCM of argon, 70-100 SCCM of nitrogen, and 30-60 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.45-0.75 Pa; c2. Set the voltage of the bias power supply to 90-130 V, the medium frequency Cr target current to 15-35 A, the medium frequency W target current to 10-30 A, and the medium frequency Si target current to 10-30 A; alternately deposit CrWSiN wear-resistant layer and CrWSiC wear-resistant layer on the surface of the transition layer of the main body of the machine part for a total of 6-12 times; alternate once every 10-18 minutes, for a total of 60-216 minutes; the film thickness is 1.85-3.8 μm.
[0009] The main body of the machine part is made of iron-based alloy or zirconium alloy, and the surface roughness of the main body of the machine part is ≤Ra0.1μm.
[0010] The present invention also provides a method for manufacturing a loom component with a coating, comprising the following steps: a. preparing a base layer: a1. Put the cleaned machine body into a vacuum furnace, and start heating and baking when the vacuum is evacuated to 0.1Pa. Set the temperature to 120-140℃ and keep the temperature constant for 40-60 minutes. a2. When the vacuum degree in the vacuum furnace reaches 4.0×10 -3 Pa-9.0×10 -3 Pa, argon gas of 70-130 SCCM is introduced into the vacuum furnace, and the vacuum degree is maintained at 0.05-0.11 Pa; a Cr arc target ion is used to bombard the surface of the main body of the machine to deposit a metal Cr bottom layer, and the arc target current is 50-90A; the bias voltage is 280-400V, and the duration is 3-11 minutes to form a bottom layer with a thickness of 0.03-0.15μm on the surface of the main body of the machine; b. Preparation of transition layer: b1. Introduce 130-220 SCCM of argon and 40-70 SCCM of nitrogen into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.35-0.65 Pa; b2. Set the voltage of the bias power supply to 100-160V, and turn on the Cr column target intermediate frequency power supply. The current of the Cr column target intermediate frequency power supply is set to 5-35A. After bombarding the base layer of the machine body with ions for 5-25 minutes, a CrN transition layer is deposited on the base layer of the machine body (Cr metal base layer); a transition layer with a thickness of 0.32-0.95μm is formed on the surface of the base layer of the machine body; c. Preparation of hardened wear-resistant layer: c1. Introduce 130-220 SCCM of argon, 70-100 SCCM of nitrogen, and 30-60 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.45-0.75 Pa; c2. Set the voltage of the bias power supply to 90-130V, the medium frequency Cr target current to 15-35A, the medium frequency W target current to 10-30A, and the medium frequency Si target current to 10-30A; alternately deposit the CrWSiN wear-resistant layer and the CrWSiC wear-resistant layer on the surface of the transition layer of the main body of the machine for a total of 6-12 times; alternate once every 10-18 minutes, for a total of 60-216 minutes; form a hardened wear-resistant layer with a thickness of 1.85-3.8μm on the surface of the transition layer of the main body of the machine; d. Surface layer preparation: d1. Introduce 130-220 SCCM of argon, 100-130 SCCM of nitrogen, and 60-90 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.35-0.65 Pa.
[0011] d2. Set the voltage of the bias power supply to 90-130V, the medium frequency Cr target current to 15-35A, the medium frequency W target current to 10-30A, and the medium frequency Si target current to 10-30A; after completing the above actions, a surface layer CrWSiNC will be deposited on the hardened wear-resistant layer of the machine body, and the deposition time is 20-60 minutes; a surface layer with a thickness of 0.3-1.1μm is formed on the hardened wear-resistant layer of the machine body.
[0012] The specific features of this solution include that the main body of the machine part is an iron-based alloy or a zirconium alloy, and the surface roughness of the main body of the machine part is ≤Ra0.1μm.
[0013] The total coating thickness is 2.5-6.0 μm.
[0014] Coating hardness 800-2300HV.
[0015] The surface roughness of the coating is ≤Ra0.2μm.
[0016] The beneficial effects of the present invention are as follows: Cr, W, Si, N and C elements are introduced into the coating, the proportions of Cr, W and Si in the coating are 30-50%, 23-33% and 27-37% respectively, the amount of nitrogen is 40-130SCCM, and the amount of acetylene is 30-90SCCM. The coating structure is more compact and firm, the coating thickness and hardness are moderate (thickness 2.5-6.0μm, hardness 800-2300HV), and the surface is fine and smooth (surface roughness ≤Ra0.2μm).
[0017] When the proportions of Cr, W, and Si in the coating are 35-45%, 25-30%, and 30-35%, respectively, the coating thickness is 3.0-5.0 μm, the coating hardness is 1200-1800 HV, and the surface roughness is ≤ Ra0.09 μm (such as Examples 1-5), the knitting needles prepared by the present invention can wear less than 0.005 mm in a 200-hour winding wear test under a tensile force of 2N. The wear exceeds the 0.006 mm wear of imported needles (Grutz) under the same test conditions, greatly improving the service life of the knitting needles and reducing the production costs of knitting companies. Moreover, the silk thread does not fuzz or break during the 200-hour test, which can ensure the quality of the product and meet the company's production needs for high-end fabrics.
[0018] When the proportions of Cr, W, and Si in the coating are 30-35%, 30-33%, and 35-37%, respectively, the coating thickness is 2.5-3.0 μm, the coating hardness is 800-1200 HV, and the surface roughness is ≤ Ra0.15 μm (such as Example 6), the knitting needle prepared by the present invention can have a wear loss of less than 0.009 mm in a winding wear test for 200 hours under a tensile force of 2N, and the yarn does not lint after 120 hours. It can be used for the production of ordinary cloth.
[0019] When the proportions of Cr, W, and Si in the coating are 45-50%, 23-25%, and 27-30%, respectively, the coating thickness is 5.0-6.0 μm, the coating hardness is 1800-2300 HV, and the surface roughness is ≤ Ra0.2 μm (such as Example 7), the knitting needle prepared by the present invention can have a wear amount of less than 0.010 mm in a winding wear test for 200 hours under a tensile force of 2N, and the yarn does not lint after 80 hours. It can also be used for the production of ordinary cloth. DETAILED DESCRIPTION
[0020] The present invention is described below in conjunction with specific implementation methods.
[0021] Embodiment 1: A loom component with a coating has a basic component body, on which a base layer, a transition layer, a hardened wear-resistant layer and a surface layer are sequentially arranged, wherein the base layer is a Cr layer, the transition layer is a CrN transition layer, the hardened wear-resistant layer is a CrWSiN and CrWSiC layer, and the surface layer is a CrWSiNC. The composition proportions of Cr, W and Si in the coating are 35%, 30% and 35% respectively. The component body is a zirconium alloy, and the surface roughness of the component body is ≤Ra0.1μm. The base layer thickness is 0.05μm. The transition layer thickness is 0.45μm. The hardened wear-resistant layer thickness is 2.0μm. A surface layer is also arranged on the hardened wear-resistant layer. The surface layer thickness is 0.5μm. The surface roughness of the coating is ≤Ra0.09μm. The total thickness of the physical vapor deposition CrWSiNC coating on the surface of the component body is 3.0μm, and the coating hardness is 1200HV.
[0022] A method for manufacturing a loom component with a coating comprises the following steps: a. Preparation of base layer: a1. Put the cleaned machine body into a vacuum furnace, and start heating and baking when the vacuum is evacuated to 0.1Pa. Set the temperature to 120℃ and keep the temperature constant for 40 minutes.
[0023] a2. When the vacuum degree in the vacuum furnace reaches 5.0×10-3Pa, 80SCCM of argon gas is introduced into the vacuum furnace, and the vacuum degree is maintained at 0.06Pa. Cr arc target ions are used to bombard the surface of the machine body to deposit a metal Cr bottom layer. The arc target current is 60A, the bias voltage is 300V, and the time is 5 minutes. A 0.05μm thick bottom layer is formed on the surface of the machine body.
[0024] b. Preparation of transition layer: b1. Introduce 150 SCCM of argon and 45 SCCM of nitrogen into the vacuum furnace to make the vacuum degree inside the vacuum furnace be 0.4 Pa.
[0025] b2. Set the voltage of the bias power supply to 110V, and turn on the Cr column target medium frequency power supply. Set the current of the Cr column target medium frequency power supply to 10A. After 10 minutes of ion bombardment on the base layer of the machine body, a CrN transition layer is deposited on the base layer of the machine body (Cr metal base layer); a transition layer with a thickness of 0.45μm is formed on the surface of the base layer of the machine body.
[0026] c. Preparation of hardened wear-resistant layer: c1. Introduce 150 SCCM of argon, 70 SCCM of nitrogen, and 35 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace be 0.5 Pa.
[0027] c2. Set the voltage of the bias power supply to 100V, the medium frequency Cr target current to 20A, the medium frequency W target current to 25A, and the medium frequency Si target current to 25A. Alternately deposit the CrWSiN wear-resistant layer and the CrWSiC wear-resistant layer on the surface of the transition layer of the main body of the machine for a total of 8 times. Alternate once every 12 minutes for a total of 96 minutes. A hardened wear-resistant layer with a thickness of 2.0μm is formed on the surface of the transition layer of the main body of the machine.
[0028] d. Preparation of surface layer: d1. Introduce 150 SCCM of argon, 105 SCCM of nitrogen, and 65 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace be 0.4 Pa.
[0029] d2. Set the voltage of the bias power supply to 100V, the medium frequency Cr target current to 20A, the medium frequency W target current to 25A, and the medium frequency Si target current to 25A. After completing the above actions, a surface layer of CrWSiNC is deposited on the hardened wear-resistant layer of the machine body. The deposition time is 30 minutes, and a surface layer with a thickness of 0.5μm is formed on the hardened wear-resistant layer of the machine body.
[0030] Example 2: The similarities between this example and Example 1 are not repeated here, except that: a loom component with a coating, the component body is a zirconium alloy low-speed slot needle (model: 51.50G104), and the Cr, W, and Si components in the coating account for 38%, 28%, and 34%, respectively. The total thickness of the physical vapor deposition CrWSiNC coating on the surface of the component body is 3.5μm, and the coating hardness is 1350HV. The surface roughness of the coating is ≤Ra0.08μm.
[0031] A method for manufacturing a loom component with a coating comprises the following steps: a. Preparation of a base layer: a1. Putting the cleaned component body into a vacuum furnace, and starting heating and baking when the vacuum is evacuated to 0.1 Pa, setting the temperature to 125°C, and keeping the temperature constant for 45 minutes.
[0032] a2. When the vacuum degree in the vacuum furnace reaches 6.0×10-3Pa, 90SCCM of argon gas is introduced into the vacuum furnace, and the vacuum degree is maintained at 0.07Pa. Cr arc target ions are used to bombard the surface of the machine body to deposit a metal Cr bottom layer. The arc target current is 65A, the bias voltage is 320V, and the time is 6 minutes. A 0.06μm thick bottom layer is formed on the surface of the machine body.
[0033] b. Preparation of transition layer: b1. Introduce 160 SCCM of argon and 50 SCCM of nitrogen into the vacuum furnace to make the vacuum degree inside the vacuum furnace be 0.45 Pa; b2. Set the voltage of the bias power supply to 120V, and turn on the Cr column target medium frequency power supply. Set the current of the Cr column target medium frequency power supply to 15A. After 13 minutes of ion bombardment on the base layer of the machine body, deposit a CrN transition layer on the base layer of the machine body (Cr metal base layer); form a transition layer with a thickness of 0.59μm on the surface of the base layer of the machine body.
[0034] c. Preparation of hardened wear-resistant layer: c1. Introduce 160 SCCM of argon, 80 SCCM of nitrogen, and 40 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.55 Pa. c2. Set the voltage of the bias power supply to 105V, the medium frequency Cr target current to 23A, the medium frequency W target current to 22A, and the medium frequency Si target current to 22A. Alternately deposit CrWSiN wear-resistant layer and CrWSiC wear-resistant layer on the surface of the transition layer of the main body of the machine for a total of 8 times. Alternate once every 13 minutes for a total of 104 minutes. A hardened wear-resistant layer with a thickness of 2.25μm is formed on the surface of the transition layer of the main body of the machine.
[0035] d. Preparation of surface layer: d1. Introduce 160 SCCM of argon, 110 SCCM of nitrogen, and 70 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace be 0.45 Pa.
[0036] d2. Set the voltage of the bias power supply to 105V, the medium frequency Cr target current to 23A, the medium frequency W target current to 22A, and the medium frequency Si target current to 22A. After completing the above actions, a surface layer of CrWSiNC is deposited on the hardened wear-resistant layer of the machine body, and the deposition time is 35 minutes; a surface layer with a thickness of 0.6μm is formed on the hardened wear-resistant layer of the machine body.
[0037] Example 3: The similarities between this example and Example 1 are not repeated here, except that: a loom component with a coating, the component body is a zirconium alloy latch needle (model: 35.60G03), and the Cr, W, and Si components in the coating account for 40%, 27%, and 33%, respectively. The total thickness of the physical vapor deposition CrWSiNC coating on the surface of the loom component is 4.0μm, and the coating hardness is 1500HV. The surface roughness of the coating is ≤Ra0.07μm.
[0038] A method for manufacturing a loom component with a coating comprises the following steps: a. Preparation of a base layer: a1. Put the cleaned component body into a vacuum furnace, start heating and baking when the vacuum is evacuated to 0.1Pa, set the temperature to 130°C, and keep the temperature constant for 50 minutes. a2. When the vacuum degree in the vacuum furnace reaches 7.0×10-3Pa, start to feed 100SCCM of argon into the vacuum furnace, and keep the vacuum degree at 0.08Pa. Use Cr arc target ions to bombard the surface of the component body to deposit a metal Cr base layer. The arc target current is 70A, the bias voltage is 340V, and the time is 7 minutes, and a base layer with a thickness of 0.07μm is formed on the surface of the component body.
[0039] b. Preparation of transition layer: b1. Introduce 170 SCCM of argon and 55 SCCM of nitrogen into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.5 Pa; b2. Set the voltage of the bias power supply to 130 V, and turn on the Cr column target intermediate frequency power supply. The current of the Cr column target intermediate frequency power supply is set to 20 A. After bombarding the bottom layer of the machine body with ions for 15 minutes, a CrN transition layer is deposited on the bottom layer of the machine body (Cr metal bottom layer); a transition layer with a thickness of 0.68 μm is formed on the surface of the bottom layer of the machine body; c. Preparation of hardened wear-resistant layer: c1. Introduce 180 SCCM of argon, 85 SCCM of nitrogen, and 45 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.6 Pa. c2. Set the voltage of the bias power supply to 110V, the medium frequency Cr target current to 25A, the medium frequency W target current to 20A, and the medium frequency Si target current to 20A. Alternately deposit CrWSiN wear-resistant layer and CrWSiC wear-resistant layer on the transition layer of the main body of the machine for a total of 9 times. Alternate once every 14 minutes for a total of 126 minutes. A hardened wear-resistant layer with a thickness of 2.5μm is formed on the surface of the transition layer of the main body of the machine.
[0040] d. Preparation of surface layer: d1. Introduce 180 SCCM of argon, 120 SCCM of nitrogen, and 80 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.5 Pa. d2. Set the voltage of the bias power supply to 110V, the medium frequency Cr target current to 25A, the medium frequency W target current to 20A, and the medium frequency Si target current to 20A. After completing the above actions, the surface layer CrWSiNC will be deposited on the hardened wear-resistant layer of the machine body, and the deposition time is 40 minutes; a surface layer with a thickness of 0.75μm is formed on the hardened wear-resistant layer of the machine body.
[0041] Example 4: The similarities between this example and Example 1 are not repeated here. The difference is that: a loom component with a coating, the main body of the component is an iron-based alloy hook needle (model: 50.75G15), and the surface roughness of the main body of the component is ≤Ra0.1μm. The composition proportions of Cr, W, and Si in the coating are 42%, 26%, and 32%, respectively. The total thickness of the physical vapor deposition CrWSiNC coating on the surface of the loom component is 4.5μm, and the coating hardness is 1650HV. The surface roughness of the coating is ≤Ra0.08μm.
[0042] A method for manufacturing a loom component with a coating, comprising the following steps: a. Preparation of a base layer: a1. Put the cleaned component body into a vacuum furnace, start heating and baking when the vacuum is evacuated to 0.1Pa, set the temperature to 140°C, and keep the temperature constant for 50 minutes. a2. When the vacuum degree in the vacuum furnace reaches 7.5×10-3Pa, start to feed 110SCCM of argon gas into the vacuum furnace, and keep the vacuum degree at 0.09Pa. Use Cr arc target ions to bombard the surface of the component body to deposit a metal Cr base layer. The arc target current is 75A, the bias voltage is 360V, and the time is 8 minutes, and a base layer with a thickness of 0.08μm is formed on the surface of the component body.
[0043] b. Preparation of transition layer: b1. Introduce 180 SCCM of argon and 60 SCCM of nitrogen into the vacuum furnace to make the vacuum degree inside the vacuum furnace be 0.55 Pa; b2. Set the voltage of the bias power supply to 140 V, and turn on the Cr column target medium frequency power supply. The current of the Cr column target medium frequency power supply is set to 25 A. After 17 minutes of ion bombardment on the base layer of the machine body, a CrN transition layer is deposited on the base layer of the machine body (Cr metal base layer); a transition layer with a thickness of 0.77 μm is formed on the surface of the base layer of the machine body.
[0044] c. Preparation of hardened wear-resistant layer: c1. Introduce 190 SCCM of argon, 90 SCCM of nitrogen, and 50 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.65 Pa. c2. Set the voltage of the bias power supply to 115V, the medium frequency Cr target current to 28A, the medium frequency W target current to 18A, and the medium frequency Si target current to 18A. Deposit alternating CrWSiN wear-resistant layer and CrWSiC wear-resistant layer on the surface of the transition layer of the main body of the machine for a total of 9 times; alternate once every 15 minutes, for a total of 135 minutes; form a hardened wear-resistant layer with a thickness of 2.75μm on the surface of the transition layer of the main body of the machine.
[0045] d. Preparation of surface layer: d1. Introduce 190 SCCM of argon, 120 SCCM of nitrogen, and 85 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.55 Pa. d2. Set the voltage of the bias power supply to 115V, the medium frequency Cr target current to 28A, the medium frequency W target current to 18A, and the medium frequency Si target current to 18A. After completing the above actions, the surface layer CrWSiNC will be deposited on the hardened wear-resistant layer of the machine body, and the deposition time is 45 minutes; a surface layer with a thickness of 0.9μm is formed on the hardened wear-resistant layer of the machine body.
[0046] Example 5: The similarities between this example and Example 1 are not repeated here, except that: a loom component with a coating, the component body is an iron-based alloy heald, and the Cr, W, and Si components in the coating account for 45%, 25%, and 30%, respectively. The total thickness of the physical vapor deposition CrWSiNC coating on the surface of the component body is 5.0 μm, and the coating hardness is 1800 HV. The surface roughness of the coating is ≤ Ra0.09 μm.
[0047] A method for manufacturing a loom component with a coating, comprising the following steps: a. Preparation of a base layer: a1. Put the cleaned component body into a vacuum furnace, and start heating and baking when the vacuum is evacuated to 0.1 Pa, set the temperature to 130°C, and keep the temperature constant for 60 minutes. a2. When the vacuum degree in the vacuum furnace reaches 8.0×10 -3 Pa, 120 SCCM of argon gas was introduced into the vacuum furnace, and the vacuum degree was maintained at 0.10 Pa. Cr arc target ions were used to bombard the surface of the main body of the machine to deposit a metal Cr bottom layer. The arc target current was 80A, the bias voltage was 380V, and the time was 9 minutes. A 0.1μm thick bottom layer was formed on the surface of the main body of the machine.
[0048] b. Preparation of transition layer: b1. Introduce 200 SCCM of argon and 65 SCCM of nitrogen into the vacuum furnace to make the vacuum inside the vacuum furnace 0.6 Pa; b2. Set the voltage of the bias power supply to 150 V, and turn on the Cr column target medium frequency power supply. The current of the Cr column target medium frequency power supply is set to 30 A. After 20 minutes of ion bombardment on the base layer of the machine body, a CrN transition layer is deposited on the base layer of the machine body (Cr metal base layer); a transition layer with a thickness of 0.9 μm is formed on the surface of the base layer of the machine body.
[0049] c. Preparation of hardened wear-resistant layer: c1. Introduce 200 SCCM of argon, 95 SCCM of nitrogen, and 55 SCCM of acetylene into the vacuum furnace to make the vacuum inside the vacuum furnace 0.7 Pa. c2. Set the voltage of the bias power supply to 120V, the medium frequency Cr target current to 30A, the medium frequency W target current to 15A, and the medium frequency Si target current to 15A. Deposit alternating CrWSiN wear-resistant layer and CrWSiC wear-resistant layer on the surface of the transition layer of the main body of the machine for a total of 10 times; alternate once every 16 minutes for a total of 160 minutes; form a hardened wear-resistant layer with a thickness of 3.0μm on the surface of the transition layer of the main body of the machine.
[0050] d. Preparation of surface layer: d1. Introduce 200 SCCM of argon, 125 SCCM of nitrogen, and 85 SCCM of acetylene into the vacuum furnace to make the vacuum inside the vacuum furnace 0.6 Pa. d2. Set the voltage of the bias power supply to 120V, the medium frequency Cr target current to 30A, the medium frequency W target current to 15A, and the medium frequency Si target current to 15A. After completing the above actions, the surface layer CrWSiNC will be deposited on the hardened wear-resistant layer of the machine body, and the deposition time is 50 minutes; a surface layer with a thickness of 1.0μm is formed on the hardened wear-resistant layer of the machine body.
[0051] Example 6: The similarities between this example and Example 1 are not repeated here. The difference is that: a loom component with a coating, the component body is a zirconium alloy high-speed slot needle, and the Cr, W, and Si components in the coating account for 30%, 33%, and 37% respectively. The total thickness of the physical vapor deposition CrWSiNC coating on the surface of the component body is 2.5μm, and the coating hardness is 800HV. The surface roughness of the coating is ≤Ra0.15μm.
[0052] A method for manufacturing a loom component with a coating comprises the following steps: a. Preparation of a base layer: a1. Put the cleaned component body into a vacuum furnace, start heating and baking when the vacuum is evacuated to 0.1Pa, set the temperature to 110°C, and keep the temperature constant for 30 minutes. a2. When the vacuum degree in the vacuum furnace reaches 9.0×10-3Pa, start to feed 70SCCM of argon into the vacuum furnace, and keep the vacuum degree at 0.05Pa. Use Cr arc target ions to bombard the surface of the component body to deposit a metal Cr base layer. The arc target current is 50A, the bias voltage is 280V, and the time is 3 minutes, and a base layer with a thickness of 0.03μm is formed on the surface of the component body.
[0053] b. Preparation of transition layer: b1. Introduce 130 SCCM of argon and 40 SCCM of nitrogen into the vacuum furnace to make the vacuum degree inside the vacuum furnace be 0.35 Pa; b2. Set the voltage of the bias power supply to 100 V, and turn on the Cr column target medium frequency power supply. The current of the Cr column target medium frequency power supply is set to 5 A. After 5 minutes of ion bombardment on the base layer of the machine body, a CrN transition layer is deposited on the base layer of the machine body (Cr metal base layer); a transition layer with a thickness of 0.32 μm is formed on the surface of the base layer of the machine body.
[0054] c. Preparation of hardened wear-resistant layer: c1. Introduce 130 SCCM of argon, 70 SCCM of nitrogen, and 30 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.45 Pa. c2. Set the voltage of the bias power supply to 90 V, the medium frequency Cr target current to 15 A, the medium frequency W target current to 30 A, and the medium frequency Si target current to 30 A. Alternately deposit CrWSiN wear-resistant layer and CrWSiC wear-resistant layer on the surface of the transition layer of the main body of the machine for a total of 6 times. Alternate once every 10 minutes for a total of 60 minutes. Form a hardened wear-resistant layer with a thickness of 1.85 μm on the surface of the transition layer of the main body of the machine.
[0055] d. Preparation of surface layer: d1. Introduce 130 SCCM of argon, 100 SCCM of nitrogen, and 60 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.35 Pa. d2. Set the voltage of the bias power supply to 90 V, the medium frequency Cr target current to 15 A, the medium frequency W target current to 30 A, and the medium frequency Si target current to 30 A. After completing the above actions, the surface layer CrWSiNC will be deposited on the hardened wear-resistant layer of the machine body, and the deposition time is 20 minutes; a surface layer with a thickness of 0.3 μm is formed on the hardened wear-resistant layer of the machine body.
[0056] Example 7: The similarities between this example and Example 1 are not repeated here, except that: a loom component with a coating, wherein the Cr, W, and Si components in the coating account for 50%, 23%, and 27%, respectively. The total thickness of the physical vapor deposition CrWSiNC coating on the surface of the component body is 6.0 μm, and the coating hardness is 2300 HV. The surface roughness of the coating is ≤ Ra0.20 μm.
[0057] A method for manufacturing a loom component with a coating comprises the following steps: a. Preparation of a base layer: a1. Put the cleaned component body into a vacuum furnace, start heating and baking when the vacuum is evacuated to 0.1Pa, set the temperature to 130°C, and keep the temperature constant for 70 minutes. a2. When the vacuum degree in the vacuum furnace reaches 4.0×10-3Pa, start to feed 130SCCM of argon into the vacuum furnace, and keep the vacuum degree at 0.11Pa. Use Cr arc target ions to bombard the surface of the component body to deposit a metal Cr base layer. The arc target current is 90A, the bias voltage is 400V, and the time is 11 minutes, and a base layer with a thickness of 0.15μm is formed on the surface of the component body.
[0058] b. Preparation of transition layer: b1. Introduce 220 SCCM of argon and 70 SCCM of nitrogen into the vacuum furnace to make the vacuum degree inside the vacuum furnace be 0.65 Pa; b2. Set the voltage of the bias power supply to 160 V, and turn on the Cr column target medium frequency power supply. The current of the Cr column target medium frequency power supply is set to 35 A. After 25 minutes of ion bombardment on the base layer of the machine body, a CrN transition layer is deposited on the base layer of the machine body (Cr metal base layer); a transition layer with a thickness of 0.95 μm is formed on the surface of the base layer of the machine body.
[0059] c. Preparation of hardened wear-resistant layer: c1. Introduce 220 SCCM of argon, 100 SCCM of nitrogen, and 60 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.75 Pa. c2. Set the voltage of the bias power supply to 130V, the medium-frequency Cr target current to 35A, the W target current to 10A, and the Si target current to 10A. Deposit alternating CrWSiN wear-resistant layer and CrWSiC wear-resistant layer on the surface of the transition layer of the main body of the machine for a total of 12 times. Alternate once every 18 minutes for a total of 216 minutes. Form a hardened wear-resistant layer with a thickness of 3.8μm on the surface of the transition layer of the main body of the machine.
[0060] d. Preparation of surface layer: d1. Introduce 220 SCCM of argon, 130 SCCM of nitrogen, and 90 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.65 Pa. d2. Set the voltage of the bias power supply to 130 V, the medium frequency Cr target current to 35 A, the medium frequency W target current to 10 A, and the medium frequency Si target current to 10 A. After completing the above actions, the surface layer CrWSiNC will be deposited on the hardened wear-resistant layer of the machine body, and the deposition time is 60 minutes; a surface layer with a thickness of 1.1 μm is formed on the hardened wear-resistant layer of the machine body.
[0061] Comparative Example 1: The similarities between this comparative example and Example 2 are not repeated here, except that: a loom component with a coating, the main body of the component is made of a zirconium alloy low-speed slot needle (model: 51.50G104), the coating does not contain W element, and the Cr and Si components in the coating account for 50% and 50% respectively. The total thickness of the physical vapor deposition CrSiNC coating on the surface of the main body of the component is 3.6μm, and the coating hardness is 1150HV. The surface roughness of the coating is ≤Ra0.27μm.
[0062] A method for manufacturing a loom component with a coating, comprising the following steps: a. Preparation of a base layer: a1. Put the iron-based alloy knitting needles after cleaning and rust removal into a vacuum furnace, and start heating and baking when the vacuum is evacuated to 0.1 Pa, set the temperature to 130°C, and keep the temperature constant for 50 minutes. a2. When the vacuum degree in the vacuum furnace reaches 7.0×10 -3 Pa, 100 SCCM of argon gas was introduced into the vacuum furnace, and the vacuum degree was maintained at 0.08 Pa. Cr arc target ions were used to bombard the surface of the main body of the machine to deposit a metal Cr bottom layer. The arc target current was 70A, the bias voltage was 350V, and the time was 7 minutes. A 0.08μm thick bottom layer was formed on the surface of the main body of the machine.
[0063] b. Preparation of transition layer: b1. Introduce 170 SCCM of argon and 55 SCCM of nitrogen into the vacuum furnace to make the vacuum degree inside the vacuum furnace be 0.5 Pa; b2. Set the voltage of the bias power supply to 130 V, and turn on the Cr column target medium frequency power supply. The current of the Cr column target medium frequency power supply is set to 15 A. After 20 minutes of ion bombardment on the base layer of the machine body, a CrN transition layer is deposited on the base layer of the machine body (Cr metal base layer); a transition layer with a thickness of 0.6 μm is formed on the surface of the base layer of the machine body.
[0064] c. Preparation of hardened wear-resistant layer: c1. Introduce 180 SCCM of argon, 85 SCCM of nitrogen, and 45 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.6 Pa. c2. Set the voltage of the bias power supply to 110V, the medium frequency Cr target current to 25A, and the medium frequency Si target current to 25A. Deposit alternating CrSiN wear-resistant layer and CrSiC wear-resistant layer on the surface of the transition layer of the main body of the machine for a total of 9 times. Alternate once every 14 minutes for a total of 126 minutes. Form a hardened wear-resistant layer with a thickness of 2.32μm on the surface of the transition layer of the main body of the machine.
[0065] d. Preparation of surface layer: d1. Introduce 180 SCCM of argon, 115 SCCM of nitrogen, and 75 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.5 Pa. d2. Set the voltage of the bias power supply to 110 V, the medium frequency Cr target current to 25 A, and the Si target current to 25 A. After completing the above actions, the surface layer CrSiNC will be deposited on the hardened wear-resistant layer of the machine body, and the deposition time is 40 minutes; a surface layer with a thickness of 0.6 μm is formed on the hardened wear-resistant layer of the machine body.
[0066] Comparative Example 2: The similarities between this comparative example and Example 3 are not repeated here. The difference is that: a loom component with a coating, the component body is a zirconium alloy latch needle (model: 35.60G03), the coating does not contain W element, and Ni element replaces Cr element. The Ni and Si components in the coating account for 50% and 50% respectively. The total thickness of the physical vapor deposition NiSiNC coating on the surface of the component body is 3.5μm, and the coating hardness is 800HV. The surface roughness of the coating is ≤Ra0.16μm.
[0067] A method for manufacturing a loom component with a coating comprises the following steps: a. Preparation of the base layer: a1. Put the cleaned knitting needles into a vacuum furnace, and start heating and baking when the vacuum is evacuated to 0.1Pa. Set the temperature to 130℃ and keep the temperature constant for 50 minutes. a2. When the vacuum degree in the vacuum furnace reaches 7.0×10-3Pa, start to feed 100SCCM of argon into the vacuum furnace, and keep the vacuum degree at 0.08Pa. Use Ni arc target ions to bombard the surface of the machine body to deposit the metal Ni base layer, the arc target current is 70A, and the bias voltage is 350V. The time is 7 minutes, and a base layer with a thickness of 0.01μm is formed on the surface of the machine body.
[0068] b. Preparation of transition layer: b1. Introduce 170 SCCM of argon and 55 SCCM of nitrogen into the vacuum furnace to make the vacuum degree inside the vacuum furnace be 0.5 Pa; b2. Set the voltage of the bias power supply to 130 V, and turn on the Ni column target medium frequency power supply. The current of the Ni column target medium frequency power supply is set to 20 A. After 15 minutes of ion bombardment on the base layer of the machine body, a NiN transition layer is deposited on the base layer of the machine body (Ni metal base layer); a transition layer with a thickness of 0.6 μm is formed on the surface of the base layer of the machine body.
[0069] c. Preparation of hardened wear-resistant layer: c1. Introduce 180 SCCM of argon, 85 SCCM of nitrogen, and 45 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.6 Pa. c2. Set the voltage of the bias power supply to 110V, the medium frequency Ni target current to 25A, and the medium frequency Si target current to 25A. Deposit alternating NiSiN wear-resistant layer and NiSiC wear-resistant layer on the surface of the transition layer of the main body of the machine for a total of 9 times. Alternate once every 14 minutes for a total of 126 minutes. Form a hardened wear-resistant layer with a thickness of 2.29μm on the surface of the transition layer of the main body of the machine.
[0070] d. Preparation of surface layer: d1. Introduce 180 SCCM of argon, 115 SCCM of nitrogen, and 75 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.5 Pa. d2. Set the voltage of the bias power supply to 110V, the medium frequency Ni target current to 25A, and the medium frequency Si target current to 25A. After completing the above actions, NiSiNC will be deposited on the hardened wear-resistant layer of the machine body for 40 minutes; a surface layer with a thickness of 0.6μm will be formed on the hardened wear-resistant layer of the machine body.
[0071] Comparative Example 3: The similarities between this comparative example and Example 4 are not repeated here. The difference is that: a loom component with a coating, the component body is an iron-based alloy hook needle (model: 50.75G15), the coating does not contain W element, Ti element replaces Cr element, and Al element replaces Si element. The composition of Ti and Al in the coating is 50% and 50% respectively. The total thickness of the physical vapor deposition TiAlNC coating on the surface of the component body is 3.6μm, and the coating hardness is 1450HV. The surface roughness of the coating is ≤Ra0.31μm.
[0072] A method for manufacturing a loom component with a coating, comprising the following steps: a. Preparation of a base layer: a1. Put the cleaned knitting needles into a vacuum furnace, start heating and baking when the vacuum is evacuated to 0.1Pa, set the temperature to 150°C, and keep the temperature constant for 60 minutes. a2. When the vacuum degree in the vacuum furnace reaches 8.0×10-3Pa, start to feed 100SCCM of argon into the vacuum furnace, and keep the vacuum degree at 0.08Pa. Use Ti arc target ions to bombard the surface of the component body to deposit a metal Ti base layer. The arc target current is 70A, the bias voltage is 350V, and the time is 7 minutes, and a base layer with a thickness of 0.08μm is formed on the surface of the component body. b. Preparation of transition layer: b1. Introduce 170 SCCM of argon and 55 SCCM of nitrogen into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.5 Pa; b2. Set the voltage of the bias power supply to 130V, and turn on the Ti column target intermediate frequency power supply. The current of the Ti column target intermediate frequency power supply is set to 20A. After ion bombarding the base layer of the machine body for 15 minutes, a TiN transition layer is deposited on the base layer of the machine body (Ti metal base layer); a transition layer with a thickness of 0.6μm is formed on the surface of the base layer of the machine body. c. Preparation of hardened wear-resistant layer: c1. Introduce 180 SCCM of argon, 85 SCCM of nitrogen, and 45 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.6Pa. c2. Set the voltage of the bias power supply to 110V, the intermediate frequency Ti target current to 25A, and the intermediate frequency Al target current to 20A. Alternating TiAlN wear-resistant layers and TiAlC wear-resistant layers are deposited on the surface of the main body of the machine for a total of 9 times. Alternating once every 14 minutes, for a total of 126 minutes. A hardened wear-resistant layer with a thickness of 2.32μm is formed on the surface of the transition layer of the main body of the machine. d. Preparation of surface layer: d1. Introduce 180SCCM of argon, 115SCCM of nitrogen, and 75SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.5Pa. d2. Set the voltage of the bias power supply to 110V, the medium frequency Ti target current to 25A, and the medium frequency Al target current to 20A. After completing the above actions, a surface layer TiAlNC will be deposited on the hardened wear-resistant layer of the main body of the machine, and the deposition time is 40 minutes; a surface layer with a thickness of 0.6μm is formed on the hardened wear-resistant layer of the main body of the machine.
[0073] Comparative Example 4: The similarities between this comparative example and Example 5 are not repeated here, except that: a loom component with a coating, the component body is an iron-based alloy heald, the Cr element is retained in the coating, the W element is replaced by the Ti element, and the Si element is replaced by the Al element. The composition ratios of Cr, Ti, and Al in the coating are 40%, 30%, and 30%, respectively. The total thickness of the physical vapor deposition TiAlNC coating on the surface of the component body is 4.0μm, and the coating hardness is 1900HV. The surface roughness of the coating is ≤Ra0.42μm.
[0074] A method for manufacturing a loom component with a coating comprises the following steps: a. Preparation of a base layer: a1. Put the cleaned knitting needles into a vacuum furnace, start heating and baking when the vacuum is evacuated to 0.1Pa, set the temperature to 130°C, and keep the temperature constant for 50 minutes. a2. When the vacuum degree in the vacuum furnace reaches 7.0×10-3Pa, start to feed 100SCCM of argon into the vacuum furnace, and keep the vacuum degree at 0.08Pa. Use Cr arc target ions to bombard the surface of the component body to deposit a metal Cr base layer, the arc target current is 70A, and the bias voltage is 350V. The time is 7 minutes, and a base layer with a thickness of 0.08μm is formed on the surface of the component body. b. Preparation of transition layer: b1. Introduce 170 SCCM of argon and 55 SCCM of nitrogen into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.5 Pa; b2. Set the voltage of the bias power supply to 130 V, and turn on the Cr column target intermediate frequency power supply. The current of the Cr column target intermediate frequency power supply is set to 20 A. After bombarding the base layer of the machine body for 15 minutes, a CrN transition layer is deposited on the base layer of the machine body (Cr metal base layer); a transition layer with a thickness of 0.6 μm is formed on the surface of the base layer of the machine body. c. Preparation of hardened wear-resistant layer: c1. Introduce 180 SCCM of argon, 85 SCCM of nitrogen, and 45 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.6 Pa. c2. Set the voltage of the bias power supply to 110 V, the intermediate frequency Ti target current to 30 A, the intermediate frequency Cr target current to 30 A, and the intermediate frequency Al target current to 25 A. CrTiAlN wear-resistant layer and CrTiAlC wear-resistant layer are alternately deposited on the surface of the main body of the machine for a total of 9 times. Alternate once every 14 minutes, for a total of 126 minutes. A hardened wear-resistant layer with a thickness of 2.52μm is formed on the surface of the transition layer of the main body of the machine. d. Preparation of surface layer: d1. Introduce 180SCCM of argon, 115SCCM of nitrogen, and 75SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.5Pa. d2. Set the voltage of the bias power supply to 110V, the medium-frequency Ti target current to 30A, the medium-frequency Cr target current to 30A, and the Al target current to 25A. After completing the above actions, a surface layer CrTiAlNC will be deposited on the hardened wear-resistant layer of the main body of the machine, and the deposition time is 40 minutes; a surface layer with a thickness of 0.8μm is formed on the hardened wear-resistant layer of the main body of the machine.
[0075] Comparative Example 5: The similarities between this comparative example and Example 1 are not repeated here, except that: a loom component with a coating, the coating does not contain Si element, and the Cr and W components in the coating account for 50% and 50% respectively. The total thickness of the physical vapor deposition CrWNC coating on the surface of the component body is 6.0μm, and the coating hardness is 2200HV. The surface roughness of the coating is ≤Ra0.49μm.
[0076] A method for manufacturing a loom component with a coating comprises the following steps: a. Preparation of a base layer: a1. Put the cleaned knitting needles into a vacuum furnace, start heating and baking when the vacuum is evacuated to 0.1Pa, set the temperature to 130°C, and keep the temperature constant for 50 minutes. a2. When the vacuum degree in the vacuum furnace reaches 7.0×10-3Pa, start to feed 100SCCM of argon into the vacuum furnace, and keep the vacuum degree at 0.08Pa. Use Cr arc target ions to bombard the surface of the component body to deposit a metal Cr base layer. The arc target current is 70A, the bias voltage is 350V, and the time is 7 minutes, and a base layer with a thickness of 0.08μm is formed on the surface of the component body. b. Preparation of transition layer: b1. Introduce 170SCCM of argon and 55SCCM of nitrogen into the vacuum furnace to make the vacuum inside the vacuum furnace 0.5Pa; b2. Set the voltage of the bias power supply to 130V, and turn on the Cr column target intermediate frequency power supply. The current of the Cr column target intermediate frequency power supply is set to 20A. After ion bombardment of the machine body base layer for 15 minutes, a CrN transition layer is deposited on the machine body base layer (Cr metal base layer); a transition layer with a thickness of 0.6μm is formed on the surface of the machine body base layer. c. Preparation of hardened wear-resistant layer: c1. Introduce 180SCCM of argon, 85SCCM of nitrogen, and 45SCCM of acetylene into the vacuum furnace to make the vacuum inside the vacuum furnace 0.6Pa. c2. Set the voltage of the bias power supply to 110V, the intermediate frequency Cr target current to 25A, and the intermediate frequency W target current to 25A. CrWSiN wear-resistant layer and CrWSiC wear-resistant layer are alternately deposited on the surface of the main body of the machine for a total of 10 times. Alternate once every 16 minutes for a total of 160 minutes. A hardened wear-resistant layer with a thickness of 4.52μm is formed on the surface of the transition layer of the main body of the machine. d. Preparation of surface layer: d1. Introduce 180SCCM of argon, 160SCCM of nitrogen, and 140SCCM of acetylene into the vacuum furnace to make the vacuum inside the vacuum furnace 0.65Pa. d2. Set the voltage of the bias power supply to 110V, the medium-frequency Cr target current to 25A, and the W target current to 25A. After completing the above actions, a surface layer CrWNC will be deposited on the hardened wear-resistant layer of the main body of the machine, and the deposition time is 40 minutes; a surface layer with a thickness of 0.8μm is formed on the hardened wear-resistant layer of the main body of the machine.
[0077] Element contents and performance parameters of examples and comparative examples (Table 1) Conclusion: 1. As can be seen from Table 1, Examples 1-5 are preferred examples, with coating thickness of 3.0-5.0 μm, coating hardness of 1200-1800 HV, and coating surface roughness ≤ 0.09 μm. Among them, Example 3 is the best. The coating surface roughness of the best example is ≤ Ra 0.07 μm.
[0078] 2. Example 6 and Example 7 are inferior examples, and the surface roughness of the coating is ≤ Ra 0.2 μm.
[0079] 3. From Examples 1-7, it is known that the coating roughness first decreases and then increases with the increase of W and Si content in the coating.
[0080] 4. When the W content in the layer is ≤27% and the Si content is ≤33%, the roughness gradually increases with the decrease of W and Si content.
[0081] 5. When the W content in the layer is ≥27% and the Si content is ≥33%, the roughness gradually increases with the increase of W and Si content.
[0082] Coating winding wear test: Use a knitting needle coating winding wear tester (Riegel). Yarn model: polyester yarn 210D. Tension 2N, speed 20m / min. Test examples 1-7 and comparative examples 1-5 for 200 hours in sequence, record the wear amount and observe the yarn fuzzing every 40 hours. Record the needle wear amount and yarn fuzzing respectively, the results are as follows: Table 2 The above data show that the coating wear of Examples 1-5 is ≤0.005 mm, and the yarn does not fuzz during the 200-hour winding test, which is a preferred solution. Examples 6 and 7 are poor examples, with coating wear of 0.009 and 0.01 mm, respectively. Moreover, the yarn of Example 6 begins to fuzz after 120 hours during the winding test, and the yarn of Example 7 begins to fuzz after 80 hours during the winding test.
Claims
1. A loom component with a coating, comprising a basic component body, on which a base layer, a transition layer, a hardened wear-resistant layer and a surface layer are sequentially arranged; wherein the composition proportions of Cr, W and Si in the coating are 30-50%, 23-33% and 27-37% respectively, the base layer is a Cr layer, the transition layer is a CrN transition layer, the hardened wear-resistant layer is a CrWSiN and CrWSiC layer, and the surface layer is a CrWSiNC.
2. The coated loom component according to claim 1 is characterized in that the composition ratios of Cr, W and Si in the coating are 35-45%, 25-30% and 30-35% respectively.
3. The coated loom component according to claim 1, characterized in that The hardened wear-resistant layer is formed by stacking CrWSiN or CrWSiC in the form of alternate deposition, with a total of 6 to 12 layers.
4. The coated loom component according to claim 1, characterized in that The thickness of the hardened wear-resistant layer is 1.85-3.8μm.
5. The coated loom component according to claim 1, characterized in that The steps for preparing the hard wear-resistant layer are as follows: c1. 130-220 SCCM of argon, 70-100 SCCM of nitrogen, and 30-60 SCCM of acetylene are introduced into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.45-0.75 Pa; c2. Set the voltage of the bias power supply to 90-130V, the medium frequency Cr target current to 15-35A, the medium frequency W target current to 10-30A, and the medium frequency Si target current to 10-30A; alternately deposit CrWSiN and CrWSiC wear-resistant layers on the surface of the knitting needle for a total of 6-12 times; alternate once every 10-18 minutes, for a total of 60-216 minutes; the film thickness is 1.85-3.8μm.
6. The coated loom component according to claim 1, characterized in that The coating has a thickness of 2.5-6.0 μm.
7. The coated loom component according to claim 1, characterized in that The main body of the machine part is made of iron-based alloy or zirconium alloy, and the surface roughness of the main body of the machine part is ≤Ra0.1μm.
8. A method for manufacturing a coated loom component, characterized in that The following steps are involved: a. Preparation of base layer: a1. Put the cleaned machine body into a vacuum furnace, and start heating and baking when the vacuum is evacuated to 0.1Pa. Set the temperature to 120-140℃ and keep the temperature constant for 40-60 minutes. a2. When the vacuum degree in the vacuum furnace reaches 4.0×10-3Pa-9.0×10-3Pa, start to feed argon gas 70-130SCCM into the vacuum furnace, and keep the vacuum degree at 0.05-0.11Pa; use Cr arc target ions to bombard the surface of the machine body to deposit the metal Cr bottom layer, the arc target current is 60-80A; the bias voltage is 280-400V, and the duration is 3-11 minutes; b. Preparation of transition layer: b1. Introduce 130-220 SCCM of argon and 40-70 SCCM of nitrogen into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.35-0.65 Pa; b2. Set the voltage of the bias power supply to 100-160V, and turn on the Cr column target intermediate frequency power supply. Set the current of the Cr column target intermediate frequency power supply to 5-35A. After bombarding the bottom layer of the machine body with ions for 5-25 minutes, deposit a CrN transition layer on the bottom layer of the machine body. c. Preparation of hardened wear-resistant layer: c1. Introduce 130-220 SCCM of argon, 70-100 SCCM of nitrogen, and 30-60 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.45-0.75 Pa; c2. Set the voltage of the bias power supply to 90-130V, the medium frequency Cr target current to 15-35A, the medium frequency W target current to 10-30A, and the medium frequency Si target current to 10-30A; alternately deposit the CrWSiN wear-resistant layer and the CrWSiC wear-resistant layer on the surface of the transition layer of the main body of the machine part for a total of 6-12 times; alternate once every 10-18 minutes, for a total of 60-216 minutes; d. Surface layer preparation: d1. Introduce 130-220 SCCM of argon, 100-130 SCCM of nitrogen, and 60-90 SCCM of acetylene into the vacuum furnace to make the vacuum degree inside the vacuum furnace 0.35-0.65 Pa; d2. Set the voltage of the bias power supply to 90-130V, the medium frequency Cr target current to 15-35A, the medium frequency W target current to 10-30A, and the medium frequency Si target current to 10-30A; after completing the above actions, a surface layer CrWSiNC will be deposited on the hardened wear-resistant layer of the machine body, and the deposition time is 20-60 minutes.
9. The method for manufacturing a coated loom component according to claim 8, wherein the composition ratios of Cr, W, and Si in the coating are 30-50%, 23-33%, and 27-37%, respectively.
10. The method for manufacturing a coated loom component according to claim 8, wherein the composition ratios of Cr, W, and Si in the coating are 35-45%, 25-30%, and 30-35%, respectively.
Citation Information
Patent Citations
Tool for manufacturing textile surfaces
CN101787628A
Metal plate bending machine
CN217251768U